Tantangan Guru dalam Mengintegrasikan Teknologi Digital pada Pembelajaran PAI di SMA Hasyim Asy'ari 1 Pucuk - Silma Murdaningtias; Muhammad Fuadhil Fahmi; Muhammad Taufiq Hidayat (AJER: Advanced Journal of Education and Religion, 2025)
The development of digital technology has had a major impact on various aspects of life, including in the education sector, one of which is learning Islamic Religious Education (PAI). This article aims to analyze the challenges faced by PAI teachers at SMA Hasyim Asy'ari 1 Pucuk in integrating digital technology in the learning process. This research uses a qualitative descriptive method with data collection techniques through interviews, observation and documentation. The research results show that there are two main challenges faced by teachers, namely limited infrastructure and a lack of understanding of the use of digital applications. Infrastructure limitations, such as a lack of technological devices and unstable internet access, hinder the use of technology in learning. Apart from that, Pai teachers also have not mastered digital applications well, which causes teachers to tend to use simple learning media such as PowerPoint or YouTube videos. Lack of training and professional development is an important factor influencing teachers' low ability to use technology. However, the potential for digital technology to improve the quality of PAI learning is very large if supported by appropriate training and the provision of adequate infrastructure. Therefore, joint efforts are needed from various parties to ensure that technology can be optimized in PAI learning, in order to improve the quality of Islamic religious education in this digital era.